Attempted self-injury and associated risk factors in patients 7 to 13 years of age admitted to the Servicio Desconcentrado Hospital Universitario Pediátrico Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2024)
Self-injury is the act by which a person intentionally causes death. The aim of this research was to determine the frequency of attempted self-injury and the associated risk factors in 35 patients aged 7 to 13 years who were admitted to the Emergency Department of the Servicio Desconcentrado Hospital Universitario Pediatrico Dr. Agustin Zubillaga during the period January 2017 to June 2022. 63% of the patients were female and 91% of them were older than 10 years old. Eighty-three percent of the patients had no pathological medical history, 97% had no psychiatric pathology and 86% of the cases showed no history of medication use. In 83% of the cases there was no family history of suicide. In the Graffar scale it was found that 61% of the cases were located in stratum IV. Ninety-one percent of the patients were studying and 77% of them were in high school. In 42% of the cases the family group consisted of 4 members. Thirty-nine percent of the patients lived with their mother and siblings and 30% with their father and siblings. Regarding the filial relationship, most of them had no relationship with their parents (33%) and 19% had a bad relationship. In 78% of the cases, some type of substance was ingested orally as a method of self-injury. In 94% of the cases, the attempt at self-injury occurred at home and was unsuccessful. Sixty-seven percent had not attempted it before and 61% had no warning beforehand. The main reasons for attempted self-harm were fights with relatives (51%) and arguments with the mother (17%).